Mantrap Based on a Novel by Sinclair Lewis - Horne, Stephen (National Film Preservation Foundation, 2011)
"Mantrap" transports urbanites into the backwoods, but it doesn't exactly follow the comic tradition of finding in the green countryside solutions to problems among men and women in the city. Such is, however, the anticipation of the two New Yorkers we first meet. A woman-addled divorce lawyer named Ralph Prescott is taken in hand by a hosiery company manager, Woodbury, to recharge his manliness through a camping trip into "the Great Outdoors" along the Manitoba-Saskatchewan border. [www.filmpreservation.org]
Keywords: DVD-Video